WHEN DOES CHARM TURN SOUR IN EARLY CAREER WORKING RELATIONSHIPS? THE RELATIONSHIP BETWEEN NARCISSISM AND LEADER-MEMBER AND MEMBER-MEMBER EXCHANGE - Birgit Schyns; Iris K. Gauglitz; Marlies Veestraeten; Steffen Nestler; Annabel-Mauve Bonnefous (Cadernos EBAPE.BR, 2024)
Abstract Internships offer the opportunity for students in higher education to have their first work experience and start building professional relationships. However, the ways in which these experiences and relationships unfold may differ significantly. In this study, we connect the dark side of personality to vocational behavior by examining the role of narcissism in early-career relationship building at work. Although narcissists often make a good first impression as being charming and extravert, this positive impression likely changes and turns negative after a period of time. While this effect has been shown in groups settings, it has yet to be replicated in a real organizational setting. We propose and test a three-way interaction model using data from interns who were rated in terms of their relationship qualities by their supervisor (Leader-Member Exchange, LMX) and their colleagues (Member-Member Exchange, MMX). Our results indicated no effect for the duration of the work relationship but an effect for groups size. Specifically, narcissistic interns working in smaller work groups were rated lower in LMX and MMX than those working in larger groups. These results have implications for future research on narcissism and the use of other ratings in organizational settings. They also have implications for the practice of hiring interns as members of staff.